Analysing an Interactive Problem-Solving Task Through the Lens of Double Stimulation - Romero, Margarida; Barma, Sylvie (Canadian journal of learning and technology, 2022)
Problem-solving activities have been studied from a diversity of epistemological perspectives. In problem-solving activities, the initial tensions of a problematic situation led to a cognitive dissonance between conflicting motives and instruments to reach the activity goal. We analyze problem-solving in the continuation of Sannino and Laitinen’s (2015) approach to the analysis of a decision-forming apparatus. The originality of this study is in consideration of the materialistic nature of double stimulation that appears during the activity of the CreaCube problem-solving task. This activity engages the participant in solving tasks with interactive robotic instruments. To solve a task, the subject is required to build interactive robotic modules into a specific configuration which will cause the artifact to move from an initial position to a predetermined final position. The conflict of stimuli in the CreaCube is strong and observable because of the tangibility of the artifact, which is manipulated by the participant into different configurations with the goal of solving the task. We discuss double stimulation in relation to the artifactual interactive affordances of educational robotics. Les activités de résolution de problèmes ont été étudiées à partir d'une diversité de perspectives épistémologiques. Dans les activités de résolution de problèmes, les tensions initiales d'une situation problématique ont conduit à une dissonance cognitive entre des motifs et des instruments contradictoires pour atteindre le but de l'activité. Nous analysons la résolution de problèmes dans le prolongement de la démarche de Sannino et Laitinen (2015) pour l'analyse d'un appareil de formation de décision. L'originalité de cette étude réside dans la prise en compte de la nature matérialiste de la double stimulation qui apparaît lors de l'activité de la tâche de résolution de problèmes CreaCube. Cette activité engage le participant dans la résolution de tâches avec des instruments robotiques interactifs. Afin de résoudre une tâche, le sujet doit construire des modules robotiques interactifs dans une configuration spécifique qui fera bouger l'artefact d'une position initiale à une position finale prédéterminée. Le conflit de stimuli dans le CreaCube est fort et observable en raison de la tangibilité de l'artefact qui est manipulé par le participant dans différentes configurations dans le but de résoudre la tâche. Nous discutons de la double stimulation en relation avec les affordances interactives artefactuelles de la robotique éducative.